Concepts of Human Nature, Personhood and Natural-Normal in New Reproductive Technology Discourses in New Zealand: Part 3: The Human in the Body - Park, Julie (Anthropologica, 2022)
I examine how concepts of human nature, person hood and natural-normal are deployed in New Zealand in interviews with people with hemophilia and in public submissions on the subject of Human Assisted Reproductive Technologies (HART). "Genetically-determined" and "relational" personhood concepts are identified in discussions of the implications of HART for the living. Discussions of HART draw on or imply contextualized concepts of "natural-normal," alternately excluding or including science from human culture and nature, and pathologizing infertility and certain family forms. My analysis employs concepts of biosociality, care and genetic citizenship.